INSTITUTIONAL MECHANISM OF ORGANIC PRODUCT MARKET FORMATION - SHARKO, Vitalii; ANDRUSENKO, Nadiia; SIRENKO, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article systematizes the constituent elements for the formation of the mechanism of development of the domestic market of organic products. Public awareness and the ever-increasing need for safe food products will make it possible to predict the growth of the volume of production/sale both on the domestic market and export of products. Taking into account the significant amount of work of scientists in the direction of developing the mechanism of formation of the market of organic products, it is important and necessary to systematize its constituent elements. The conditions for the development of organic production are compliance of the organic system of agriculture and agricultural products with certain standards, which makes it possible to label products accordingly and sell them as organic. In this context, the development of the mechanism of market formation and stimulation of the development of agricultural enterprises - producers of organic products - is of great importance. Based on the understanding of the essence of the institutional mechanism presented in scientific developments, we can formulate our own vision of the institutional mechanism of the formation of the organic agriculture products market. This mechanism is a system of ensuring the interaction of market subjects, institutions of the state, law, power, competition, trust, aimed at supporting the processes that lead to filling the market with organic food, preserving the environment and developing the national economy. The scheme presented in the article reveals the relationship and interrelationship of all elements of the institutional mechanism, namely: the goal and methods of its achievement; objects (producers and consumers of organic products) to which the action of the subjects of the institutional mechanism (bodies of state power, local self-government, public organizations, management of enterprises) is directed with the help of tools (legislative, administrative, organizational, informal) and through the mediation of formal and informal institutions (institutions of the state, law, power, competition, trust, etc.). The proposed interpretation of the institutional mechanism of the formation of the market for organic agriculture products made it possible to single out the main processes, through the effective implementation of which the goal should be achieved - saturation of the market with organic food, preservation of the environment, harmonious human development.